The Guidance and Supervision Function of the Regional Government of West Kalimantan Province regarding the Accessibility of the Legal Documentation and Information Network (JDIH) of Regencies/Cities within its Region - Yustika Irianita Fanty (Law Research Review Quarterly, 2025)
As a means of disseminating information, JDIH provides convenience for the public to search for and access the full text of provisions of laws and regulations, such as laws, government regulations, presidential decrees, and regional regulations. However, in its implementation, the use of JDIH owned by each Regional Government cannot be optimally utilized by the society. Because there are still several official JDIH pages belonging to the Regional Government that cannot be accessed by the public. This research aims to determine the extent of the guidance and supervision function of the West Kalimantan Provincial Government regarding the accessibility of JDIH Districts/Cities in the West Kalimantan Province. This research is research with a juridical-normative method, with legal material sources consisting of primary legal materials and secondary legal materials. The data collection technique used is primary data collection through interviews with informants and data sourced from each JDIH website of the Regency/City Government in West Kalimantan Province. The results of the study focused on the lack of support given to JDIH which has a strategic role in government that supports organizational performance and as a form of government presence providing access to information to the public through an electronic system that is easily accessible, fast and simple.